The Importance of Maintaining Fishing Boats and Understanding Life Safety at Sea for Fishermen in East Sapa Village - Dedtri Anwar; Frisca Mareyta Pongoh; Yustiani Frastika; Santun Irawan; Joseph R Rengga (Lembaga Pengembangan Kinerja Dosen, 2024)
The importance of fishing boat maintenance cannot be underestimated. A well-maintained vessel not only increases efficiency in fishing operations, but also minimizes the risk of accidents at sea. Ship maintenance covers various aspects, from regular engine inspections, repairing damaged hulls, to ensuring that all safety equipment is in good condition. The purpose of this study is to increase the awareness and understanding of fishermen in East Sapa Village regarding the importance of ship maintenance and life safety at sea. This research method uses a qualitative method with a short description of the analysis. The results of this study show that although the fishermen of East Sapa Village have a basic awareness of the importance of boat maintenance and safety at sea, they face a variety of significant challenges, including limited resources, limited technical knowledge, and lack of relevant training. Financial and material constraints hinder the implementation of thorough ship maintenance, while a varied understanding of safety indicates the need for more in-depth education. Strong community cooperation and greater government support, including the provision of resources and training programs, are essential to address these issues and improve the well-being and safety of fishermen.